Appraisal of Thyroidectomy in Outlying Tertiary Care Hospital (Global Journal of Medical Research, 2020)
Abstract not found
Keywords: hemithyroidectomy (HT); total thyroidectomy (TT); completion thyroidectomy (CT); selective neck dissection (SND)